OPTIMIZATION OF DIMENSION AND SHAPE FOR BALL VALVE BODY IN FIRE SAFE DESIGN - GHEORGHIŢA TOMESCU; RADU IATAN; IULIANA IAŞINICU (STAMATE) (Journal of Engineering Studies and Research)
The fire safe valves are designed for petroleum and petrochemical complexes and allied industries because working fluid characteristics result in a high fire risk, detonation and / or explosion. Fire Safe Certification is achieved through a standardized fire testing. This article aims to show how to optimize the shape and size of the main body of a ball valve in sequence CAD – FEM - testing and evaluation of the performance of valves when exposed to fire. This analysis is necessary because fire testing is expensive to verify and the validation of constructive solutions helps reduce production costs and achieve fire prevention through design.